(untitled) (Veterinary Science, 2024)
The aim of this study was to determine the effects of different disbudding methodologies in Holstein calves on behavioral and physiological parameters related to pain. Twenty-five calves under artificial rearing with an average of 22 ± 3 days of age and 48.9 ± 8.8 kg of live weight were randomly assigned to three treatments: Tc, control disbudding with a thermal method using hot iron, Ta: disbudding with hot iron + flunixin meglumine (2.2 mg/kg intramuscular, 20 minutes prior to the procedure and Tp: disbudding using caustic paste. After disbudding and for 30 minutes, the number of times that each animal performed the following behaviors was recorded: Shakes head, scratches the head, rubs the head, presses the head, shakes the body, grooms, jumps, runs and bleats. Then the heart and respiratory rates were measured. In the Tp group the frequencies of shaking the head (p < 0. 0003), scratching the head (p< 0.0009), rubbing the head (p<0.0011), jumping (p<0.0005) and running (p<0.0002), were significantly higher than in the groups Ta and Tc. The heart rate of the Tp calves was significantly (p< 0.0013) higher (125.5 ± 13.5) than that of Ta (85.3 ± 24.2) and Tc (87 .0 ±18.8), as well as the respiratory rate, resulting in Tp (70.6 ±8.6) higher (p<0.02) than Ta (37.7 ± 20.9) and Tc (40.0 ± 21.2). The results showed that the use of caustic paste for disbudding has greater negative implications in terms of behavioral and physiological responses with respect to the thermal method and that under the conditions of this trial the intramuscular administration of flunixin meglumine did not show beneficial effects.